Maler und das Theater im 20.Jahrhundert : live ! Performance, Theater, Tanz, Musik. - Baixas, Joan; Beaujean, Alfred; Birr, Horst; Günther, Helmut; Ingold, Felix Philipp; Kerber, Bernhard; Nessler, Nikolaus; Tarnow, Christopher; Williams, Emmett; Kulturgesellschaft Frankfurt mbH (Frankfurt : Kulturgesellschaft Frankfurt mbH, 1986)
Balser, Ursula ; Barlach, Ernst ; Baumann, Walter E. ; Ben ; Böcklin, Arnold ; Bohner, Gerhard ; Dittrich, Andreas ; Foregger, Nikolai ; Forsythe, William ; Gauguin, Paul ; Heinisch, Barbara ; Kandinsky, Wassily ; Klauke, Jürgen ; Kutscher, Vollrad ; Litscher, Hans-Peter ; Marek, Raoul ; Miro, Joan ; Mussorgsky, Modest ; Nieslony, Boris ; Noland, Kenneth ; Perlmann, Cara ; Picasso, Pablo ; Rousseau, Henri ; Santarossa, Hella ; Schlemmer, Oskar ; Silber, Alex ; Steffen, Arno ; Tarnow, Christopher ; Uecker, Günther ; Uhlig, Gerald ; Williams, Emmett
Duits
Die Maler und das Theater im 20.Jahrhundert : live ! Performance, Theater, Tanz, Musik. Schirn Kunsthalle Frankfurt, Kulturgesellschaft Frankfurt mbH, 28.02.1986 - 19.05.1986
boek